2021
DOI: 10.3389/fnut.2021.641227
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Hormone Profiles in Breast Milk From Mothers of Moderate-Late Preterm Infants Are Associated With Growth From Birth to 4 Months in a Sex-Specific Manner

Abstract: Background: Differing environmental conditions experienced by mother-infant dyads may influence composition of the milk received by the infant. As a consequence, diverse milk compositional profiles may contribute to different postnatal outcomes, especially in infants facing adverse perinatal environments. We investigated whether variability in milk concentrations of key metabolic hormones is associated with different growth outcomes in infants born preterm, a perinatal complication known to impact on infant gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…We did not find any associations between neither HM leptin nor adiponectin and any of the growth outcomes, and the literature states conflicting results within this research area (25). Galante and colleagues found leptin concentrations in HM 5 days postpartum positively associated with infant fat mass at discharge for moderate-late preterm infants, however HM leptin was negatively associated with fat mass at 4 months' corrected age (57). A considerable unknown factor is the plausible mechanism assumed when posing hypotheses regarding HM composition and associations with infant outcomes.…”
Section: Appetite-regulating Hormones In Human Milk and Infant Outcom...mentioning
confidence: 99%
“…We did not find any associations between neither HM leptin nor adiponectin and any of the growth outcomes, and the literature states conflicting results within this research area (25). Galante and colleagues found leptin concentrations in HM 5 days postpartum positively associated with infant fat mass at discharge for moderate-late preterm infants, however HM leptin was negatively associated with fat mass at 4 months' corrected age (57). A considerable unknown factor is the plausible mechanism assumed when posing hypotheses regarding HM composition and associations with infant outcomes.…”
Section: Appetite-regulating Hormones In Human Milk and Infant Outcom...mentioning
confidence: 99%
“…For example, leptin levels in preterm infants correlate with breast milk leptin levels [ 346 ]. One study reported that milk leptin concentrations on postnatal day 5 were positively associated with fat mass at NICU discharge, but negatively associated with fat mass at 4 months’ corrected age [ 347 ]. Another study found that total milk leptin intake in the first 28 postnatal days was positively associated with weight gain velocity and weight z-score at birth to 36 weeks’ postmenstrual age (PMA) [ 348 ].…”
Section: Effects Of Nutritional and Pharmacologic Interventions On Gr...mentioning
confidence: 99%
“…In this study, adiponectin intake from milk was associated with greater length z-scores but lower head circumference z-scores at 36 weeks’ PMA. Another study found no correlation between milk adiponectin and growth outcomes [ 347 ]. Milk IGF-1 concentrations are associated with fat-free mass at 4 months’ corrected age, while milk ghrelin concentrations are associated with neonatal weight gain and linear growth [ 347 , 349 ].…”
Section: Effects Of Nutritional and Pharmacologic Interventions On Gr...mentioning
confidence: 99%
See 1 more Smart Citation